Risk communication management through Facebook: Exploratory analysis of the initial strategies of 12 Latin American governments in the COVID 19 pandemic - Cárdenas Ruiz, Juan David (2021)
The Sars-Cov 2 pandemic made governments rethink the forms of communication. Discursive strategies regarding the use of media and forms of communication focused on understanding the pandemic and communicating the risk. This article analyzes the cases of twelve Latin American countries regarding the Executive's ability to adapt to risk communication, as the main tool for modifying habits and behaviors to prevent risk, as well as the potential use they gave to the social networks to establish immediate and real-time contact with its citizens. For this purpose, the study is theoretically based on the studies of risk communication, Agenda Setting, Framing and social networks. The investigation took the official Facebook accounts of the Presidency, Ministries / organizations in charge of public health and presidential personal accounts to analyze the content of the publications, from the first case of contagion reported in each country, until June 30, date of cut. A stratified random sampling was carried out for each country, resulting in a total of 1420 publications analyzed. The main results range from the multiplication of followers of followers to these official accounts, in the first 3 months of the arrival of the virus in each country, to the five themes and approaches that each nation managed to install in the agenda to communicate to its inhabitants the phenomenon. A difference can be identified between the speech that is handled in the social network and that perceived in the presidential pronouncements in the traditional media.